In situ U-Pb geochronology of baddeleyite-zircon pairs using laser-ablation ICPMS; the case study of quartz gabbro from Varney Nunatak (central Victoria Land, Antarctica) - Renna M. R.; Tiepolo M.; TRIBUZIO, RICCARDO (European Journal of Mineralogy, 2011)
In situ U-Pb geochronology was carried out by laser-ablation ICPMS on baddeleyite and zircon from a quartz gabbro of the Varney Nunatak intrusion (central Victoria Land, Antarctica). Back-scattered electron images reveal that baddeleyite grains from the investigated rock are partially substituted by zircon. Baddeleyite replacement by zircon is attributed to a late magmatic reaction between early fractionating minerals (plagioclase + sub-ophitic clinopyroxene + ilmenite + baddeleyite) with a silica oversaturated melt enriched in volatiles and incompatible elements. The development of fine-grained aggregates of clinopyroxene + amphibole + ilmenite around sub-ophitic clinopyroxene provides further evidence for this reaction. Homogeneous domains of baddeleyite were analysed by laser-ablation ICPMS and yielded crystallisation ages for the quartz gabbros of 488 +/- 3 Ma. U-Pb analyses on zircon define a population at 486 +/- 6 Ma, coeval with the U-Pb baddeleyite crystallization age, and a population at 525 +/- 10 Ma, representing an inherited component. This finding indicates that the parent magma of the quartz gabbro was contaminated with upper crustal rocks. The gabbroic rocks of Varney Nunatak are associated with peraluminous granites and late basalt dykes. The similar whole-rock and clinopyroxene major and trace element concentrations in the quartz gabbros and basalts is suggestive for a genetic relationship. The emplacement age, whole-rock compositions and highly enriched Nd isotope signature [εNd (488 Ma) of -7.7 to -6.8] of the Varney Nunatak association are similar to those of other igneous units from central Victoria Land. The association developed during the post-collisional phase of the Ross orogeny.